Toward a culture of engagement: leveraging the enterprise social network - Alistoun, Garth (Rhodes University, Faculty of Commerce, Department of Information Systems, 2014)
This research aims to provide a theory of enterprise social networking that generates and/or sustains a culture of employee engagement within a chosen South African private sector company. Based on an extensive review of interesting literature and the application of a grounded theory process in a chosen case, this research work provides a theory of enterprise social networking sustaining and growing employee engagement together with an explanatory theoretical framework that makes the theory more practical. Employee engagement is defined as "the harnessing of organisation member's selves to their work roles; in engagement people employ and express themselves physically, cognitively, and emotionally during role performances." This research regards employee engagement as a three part concept composed of a trait (personality/cognitive) aspect, a state (emotional) aspect, and a behavioural aspect. Research has shown that employee engagement has an unequivocal positive impact on business outcomes, such as profitability, business performance, employee retention and productivity. Employee engagement can be regarded as a culture if it is abundant within the organization's employee population. Gatenby et al. (2009) propose that employee engagement is fostered by creating the desire and opportunity for employees to connect with colleagues, managers and the wider organisation. This standpoint is supported by Kular et al. (2008) who state that the "key drivers of employee engagement identified include communication, opportunities for employees to feed their views upward and thinking that their managers are committed to the organisation." Further indicators of employee engagement include strong leadership (particularly in the form of servant leadership), accountability, a positive and open organisational culture, autonomy, and opportunities for development. One of the key facets of employee engagement is connection. A complementary definition of social media, an umbrella under which enterprise social networks fall, is that "(it) is more of a relationship channel, a connection channel. Each and every tweet, update, video, post, is a connection point to another human being. And it's the other human being who will determine your worth to them." Social media provides participants with access to a larger pool of resources and relationships than they would normally have access to. This enlarged relationship/resource pool is a result of expanding human and social capital enabled through social media tools. In order to produce a theory of enterprise social networking sustaining and growing a culture of employee engagement a rigorous grounded theory methodology coupled with a case study methodology was applied. The case study methodology was used to identify a suitable research site and interesting participants within the site while the grounded theory process was used to produce both qualitative and quantitative data sets in a suitability rigorous fashion. The corroborative data was then used to discover and define the emergent theory.
Keywords: Communication in organizations -- South Africa; Business communication -- South Africa; Social media -- South Africa -- Case studies; Leadership -- South Africa -- Case studies; Human capital -- Management; Personnel management; Organizational effectiveness